ANALISIS NILAI TAMBAH DAN OPTIMASI KEUNTUNGAN PRODUKSI OLAHAN KERANG KAMPAK (STUDI KASUS PADA UMKM BUNDA SURABAYA) - Ningsih, Afifah Rohmania; Indah, Pawana Nur; Fitriana, Nisa Hafi Idhoh (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This research was conducted at UMKM Bunda Surabaya, Surabaya City, with a focus on value-added analysis and profit optimization of processed shellfish production. The research method used was a case study with non-probability sampling, and data collection through interviews, questionnaires, observation, and secondary data. Data analysis was carried out descriptively and quantitatively, including the calculation of production costs, revenues, and profits. The Hayami method was used to calculate added value, while the simplex method was used for production profit optimization. The results showed that Bunda Surabaya MSMEs earned profits from the production of shredded clams, clam sticks, and clam chili sauce, with a fairly high added value. The highest profit was obtained from the clam sauce product amounting to Rp. 775,201 per one production process. The added value of shredded clams is Rp. 94,726 per kg of raw material with a value-added ratio of 63.15%. This research is expected to provide benefits for the shellfish processing industry and improve the welfare of the fishing community.